Classroom injustice and university students’ cyberloafing: the mediating role of neutralization techniques - Han, Zhiyong; Yang, Zhiyong; Huang, Ziwei (Frontiers in Psychology, 2025)
IntroductionCyberloafing in the classroom has been linked to adverse educational outcomes, undermining students’ learning and frustrating instructors. From a neutralization perspective, students may justify deviant acts when they perceive injustice. This study examined how perceived classroom justice relates to students’ intention to cyberloaf and tested the mediating roles of two neutralization techniques: condemning the condemners and appealing to higher loyalties.MethodsWe conducted a questionnaire study with 310 university students recruited from multiple universities in the central and eastern regions of China. Measures assessed perceived classroom justice, intention to cyberloaf, and the neutralization techniques of condemning the condemners and appealing to higher loyalties. We tested a mediation model linking classroom justice to cyberloafing intention through these neutralization techniques.ResultsPerceived classroom justice was negatively associated with students’ intention to cyberloaf. Classroom justice also negatively predicted condemning the condemners and appealing to higher loyalties. Furthermore, both neutralization techniques mediated the relationship between classroom justice and intention to cyberloaf.DiscussionFindings suggest that higher levels of classroom justice may deter students’ cyberloafing partly by weakening justificatory neutralizations. These results highlight the importance of enhancing classroom justice to reduce cyberloafing behaviors. Educators are encouraged to adopt strategies that strengthen perceptions of fairness in classroom practices.